Evaluation of vertical ground reaction forces in three different judo hip throwing techniques in novice and advanced Greek athletes - Zaggelidis, G.; Lazaridis S. (Medicina dello Sport, 2012)
Aim. The purpose of this study was to analyze the vertical ground reaction forces [VGRFz] of three different throwing hip techniques (Harai-Goshi-Hip Sweep Throw [HG], Hane Goshi-Hip Spring Throw [HnG] and Uchi Mata-Inner Thigh Throw [UM]) in novice and high level Greek judo athletes.